Do institutional blockholders influence corporate investment? Evidence from emerging markets (2017)
This paper examines the relation between firm investment ratios and institutional blockholder ownership for a sample of 6,300 publicly traded firms of 16 large emerging markets for the 2005-2014 period. Results show that independent, long-term, and local institutional investors boost investment ratios, consistent with the monitoring role and blockholder voice intervention hypotheses. The presence of institutional blockholders, regardless their monitoring involvement, reduces firm cash flow sensitivity ratios and thus decreasing firms' financial constraints.